GBP5 Is an Interferon-Induced Inhibitor of Respiratory Syncytial Virus - Li, Zhaolong (J Virol, 2020)
Guanylate binding protein 5 (GBP5) belongs to the GTPase subfamily, which is mainly induced by interferon gamma (IFN-γ) and is involved in many important cellular processes, including inflammasome activation and innate immunity against a wide variety of microbial pathogens. However, it is unknown whether GBP5 inhibits respiratory syncytial virus (RSV) infection. In this study, we identified GBP5 as an effector of the anti-RSV activity of IFN-γ and found that in children, the weaker immune response, especially the weaker IFN-γ response and the decreased GBP5 expression, leads to RSV susceptibility. Furthermore, we revealed that GBP5 reduced the cell-associated levels of the RSV small hydrophobic (SH) protein, which was identified as a viroporin. In contrast, overexpression of the SH protein rescued RSV replication in the presence of GBP5. The GBP5-induced decrease in intracellular SH protein levels is because GBP5 promotes the release of the SH protein into the cell culture. Moreover, the GBP5 C583A mutants with changes at the C terminus or the GBP5 ΔC mutant lacking the C-terminal region, which impairs GBP5 localization in the Golgi, could not inhibit RSV infection, whereas the GTPase-defective GBP5 maintained RSV inhibition, suggesting that Golgi localization but not the GTPase activity of GBP5 is required for RSV inhibition. Interestingly, we found that RSV infection or RSV G protein downregulates GBP5 expression by upregulating DZIP3, an E3 ligase, which induces GBP5 degradation through the K48 ubiquitination and proteasomal pathways. Thus, this study reveals a complicated interplay between host restrictive factor GBP5 and RSV infection and provides important information for understanding the pathogenesis of RSV. IMPORTANCE RSV is a highly contagious virus that causes multiple infections in infants within their first year of life. It can also easily cause infection in elderly or immunocompromised individuals, suggesting that individual differences in immunity play an important role in RSV infection. Therefore, exploring the pathogenic mechanisms of RSV and identifying essential genes which inhibit RSV infection are necessary to develop an effective strategy to control RSV infection. Here, we report that the IFN-inducible gene GBP5 potently inhibits RSV replication by reducing the cell-associated levels of the RSV small hydrophobic (SH) protein, which is a viroporin. In contrast, the RSV G protein was shown to upregulate the expression of the DZIP3 protein, an E3 ligase that degrades GBP5 through the proteasomal pathway. Our study provides important information for the understanding of the pathogenic mechanisms of RSV and host immunity as well as the complicated interplay between the virus and host.